2015
DOI: 10.1007/s11096-015-0182-4
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist intervention in patients with renal impairment

Abstract: Community pharmacists identified 40 % of DRP related to CKD prescriptions, leading to prescription modification by GPs in a third of the cases. These interventions are likely to decrease drug-related morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 16 publications
4
30
0
1
Order By: Relevance
“…While almost half of the studies were cross‐sectional, 21 studies implemented interventions to reduce IP . Of these interventions, almost half were manual decision aids (n = 10), others were computerised decision support aids to physicians and pharmacists (n=9) and in the remaining studies (n=2), physicians were prompted with calculated eGFR values (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While almost half of the studies were cross‐sectional, 21 studies implemented interventions to reduce IP . Of these interventions, almost half were manual decision aids (n = 10), others were computerised decision support aids to physicians and pharmacists (n=9) and in the remaining studies (n=2), physicians were prompted with calculated eGFR values (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐three of the included studies were rated as moderate or high quality (can be accessed on supporting information). All studies defined their inclusion criteria and evaluated IP objectively with comparators described clearly, where applicable .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study conducted in the residents of aged care facilities; it has shown that DRPs were mostly dose-related [28]. Previous studies have shown that CG and MDRD perform better with varied scenarios [29][30][31][32]. However, the study on meropenem found no difference between CG and MDRD [33].…”
Section: Discussionmentioning
confidence: 97%